Arsenic Content in Rice in Ghana: A Potential Health Hazard - Benjamin, Bartels; Nkuma, Akua; Patrick Yao, Gadzekpo Victor (International Journal of Environment, Agriculture and Biotechnology, 2023)
Background and objectives: Arsenic found mostly in rice and rice products is a carcinogen that affects the skin and internal organs. In recent times, concerns have been on the characteristic chronic concentration of this metal in rice even as FAO forecast increasing global production of rice. The aim of this study is to determine arsenic concentration in both local and imported rice patronized by consumers in the Central Region of Ghana. Method: A total of thirty-three samples comprising of seven locally produced rice and four imported brands were collected in three months from various outlets in Ghana. The samples were separately milled, digested and then filtered. The clear solution was used to run the arsenic test using A.A.S. Results: The local rice had concentration ranging from 0.256-0.420 mg/kg As, while the imported recorded 0.410-0.505 mg/kg As. The values obtained exceeded CODEX value of arsenic concentration in rice. Conclusion: Consumers of rice in Ghana are potentially at risk of arsenic related diseases.